Student Engagement in the Classroom: Stance of Elementary Teachers - Oliva, Irish Mae C. (International Journal of Research in Interdisciplinary Studies, 2024)
This phenomenological study explored the experiences of teachers in engaging students in the classroom at San Isidro District, Division of Davao del Norte. This also investigated their coping mechanisms from the challenges they encountered, and their insights drawn from the findings of this study. Qualitative–phenomenological study was employed in exploring the views of the ten (10) elementary teachers of which primary instrument of data gathering was through in- depth interview. Major findings indicated that the themes include the experiences of teachers were teaching strategies and techniques, challenges in student engagement, and impact of teacher-student relationship. Further, in navigating the complexities of student engagement, teachers often encounter challenges that prompt the development of coping mechanisms to sustain effective classroom dynamics. This exploration delves into key themes that illuminate adaptive pedagogical strategies, social-emotional support and well-being, and professional development and collaboration. Lastly, in examining the insights of teachers in engaging students, we delve into the multifaceted strategies employed by educators to create dynamic and effective learning environments. This exploration encompasses themes such as pedagogical innovation and flexibility, building positive teacher-student relationships, and the promotion of inclusivity and interactivity within the classroom. Effectively engaging students in the classroom holds profound implications for the overall learning experience and academic success. The manner in which teachers facilitate student engagement influences not only the acquisition of knowledge but also shapes students' attitudes toward learning and their overall educational journey.